Cybersecurity in Satellite Communication Networks: Key Threats and Neutralization Measures - Aditi Ranjit Kumar Verma (IEEE Open Journal of the Communications Society, 2025)
The proliferation of satellite mega-constellations, such as SpaceX’s Starlink and NewSpace initiatives, particularly CubeSat deployments, and their integration into terrestrial 5G/6G networks have transformed space-based communications. While this technological convergence has brought numerous advantages, it has also introduced a new vector of cybersecurity threats to both traditional satellite infrastructure and novel small-satellite architectures. Owing to their broadcast nature and extensive coverage area, satellite signals are inherently susceptible to jamming, spoofing, and eavesdropping, rendering them appealing targets for malicious actors. Moreover, satellites operate under power, computational, and bandwidth limits, which restrict the implementation of resource-intensive security measures. Therefore, it is necessary to develop robust and lightweight security frameworks capable of countering threats across multiple orbital domains, communication protocols, and network integration points. This paper presents a hybrid research contribution that combines a systematic survey of key cyber threats with novel conceptual and practical security frameworks for satellite communication (SATCOMs) networks. It weaves threats, defenses, and governance into a coherent scaffold that follows the entire SATCOM stack–space, ground, and user–across all orbits. Unlike most previous studies–which treat countermeasures in a fragmented manner with limited synergy across layers–this study presents cyber threats using the confidentiality-integrity-availability (CIA) triad and presents a multilayered security framework that combines physical-layer hardening, quantum-resilient encryption, and AI-driven analytics, supported by a governance framework aligned with standards, within one integrated workflow. The undertaken approach uniquely addresses prevention, defense, resilience, and collaboration through detailed countermeasures. This bridges the gap between isolated security solutions and the interconnected nature of modern SATCOM ecosystems. The analysis of the research reveals that prioritizing lightweight AI, quantum resilience, and cross-layer security by real-world SATCOM operators and agencies is critical for securing next-generation SATCOMs against sophisticated cyber-attacks. Moreover, the convergence of SATCOMs with 5G/6G, AI, and quantum technologies requires interdisciplinary research to address the interoperability, scalability, and ever-increasing cyber threats in SATCOMs.